2021
DOI: 10.1021/acs.orglett.1c03242
|View full text |Cite
|
Sign up to set email alerts
|

Difluoromethyl Radical Triggered Tandem Reaction of N-Allyl Amides to Difluoromethylated β-Amino Alcohols by Photoredox Catalysis

Abstract: An elegant tandem reaction process for transferring N-allyl amide into CF2H-β-amino alcohol is described. This approach proceeded smoothly under visible light irradiation in the presence of a 3 mol % Ir complex, exhibiting a broad substrate scope and functional group tolerance, and a variety of CF2H-β-amino alcohols were readily accessed in good to excellent yields under mild conditions. The reliable mechanistic studies revealed that sequential difluoromethyl radical addition/carbocation trap/rearrangement is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Additionally, a radical clock experiment revealed that rearranged product 6 from vinylcyclopropane 5 was isolated in 17% yield, along with an obviously decreased yield (18%) of 4aa (Scheme B). According to these results and our previous report, a plausible reaction mechanism was proposed in Scheme C. Initially, difluoromethylating reagent 3 is reduced by the excited-state PC* to deliver the CF 2 H radical and PC + , and then CF 2 H radical adds to ethyl acrylate 2 , leading to intermediate radical I, which sequentially adds to carbazole to render intermediate radical II, followed by a SET process to afford carbon cationic species III, along with the renewal of PC.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Additionally, a radical clock experiment revealed that rearranged product 6 from vinylcyclopropane 5 was isolated in 17% yield, along with an obviously decreased yield (18%) of 4aa (Scheme B). According to these results and our previous report, a plausible reaction mechanism was proposed in Scheme C. Initially, difluoromethylating reagent 3 is reduced by the excited-state PC* to deliver the CF 2 H radical and PC + , and then CF 2 H radical adds to ethyl acrylate 2 , leading to intermediate radical I, which sequentially adds to carbazole to render intermediate radical II, followed by a SET process to afford carbon cationic species III, along with the renewal of PC.…”
Section: Resultssupporting
confidence: 65%
“…Very recently, Wong et al explored a visible-light photoredox-catalyzed three-component reaction of quinoxalin-2­(1 H )-ones, alkene, and BrCF 2 CO 2 Et to access gem -difluoromethyl-containing quinoxalin-2­(1 H )-ones . In line with our continuous efforts in the development of fluoroalkylating reagents and their applications, as well as the synthesis of fluorinated biologically active compounds, the S -(difluoromethyl)­sulfonium salt developed by our group has proved to be a good difluoromethyl radical ( • CF 2 H) precursor and could be applied to a wide variety of • CF 2 H transformations. We herein report a facile and practical approach for the synthesis of CF 2 H-containing carbazoles via a visible-light photoredox-catalyzed three-component reaction of carbazoles with styrenes and S -(difluoromethyl)­sulfonium salt (Scheme c), and a broad range of fluoroalkyl-functionalized carbazole derivatives were readily synthesized in moderate to good yields by mild visible-light-photoredox catalysis.…”
Section: Introductionmentioning
confidence: 89%
“…In spite of the aforementioned preliminary progress, the direct C(sp 3 )–H difluoromethylation remains largely underdeveloped and highly desirable as one of the most straightforward and promising strategies. To address this topic and challenge, we decided to develop an elegant and highly efficient solution by using our bench-stable S-(difluoromethyl)diarylsulfonium salts 2 , 10 which have proved to be good difluoromethyl radical precursors under photoredox catalysis, 13 as well as electrophilic difluoromethylating reagents and difluorocarbene precursors. 10,14 On the other hand, the photoredox-catalyzed reaction is becoming a more and more popular synthetic version for incorporating the fluoroalkyl group into various organic molecules via a radical pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Liu and co-workers described the oxydifluoromethylation of N -allyl amides with an S -(difluoromethyl)sulfonium salt under photoredox catalysis with the aid of 3 mol% of fac -Ir III (ppy) 3 (Scheme 28). 39 Under the optimum conditions, a variety of CF 2 H-β-amino alcohols were obtained in good to excellent yields. Mechanistic investigations demonstrated that a sequential process of difluoromethyl radical addition, oxidation, intramolecular carbocation trapping and rearrangement reaction was involved.…”
Section: Difluoromethylation Of Alkenesmentioning
confidence: 99%